Kontekstualisasi Nilai-Nilai Adat Toana Dalam Pembelajaran Sejarah (Studi pada Siswa SMA Negeri 10 Kota Pontianak) - Edwin Mirzachaerulsyah; Andang Firmanysah; Astrini Eka Putri (Jayapangus Press, 2022)
Adat Toana is part of the historiography of the Mempawah Kingdom where the values ​​in Adat Toana describe the heterogeneous character and characteristics of the Mempawah community, this can be a contextual history learning material for students because it can link the past and its causality for the present. This study aims to (1) what are the values ​​in Adat Toana (2) how to contextualize Adat Toana in learning history. This study uses a qualitative approach with a descriptive study. Data obtained from observations, interviews and documentation studies. The results of this study indicate that Adat Toana has cultural, social and historical values. In teaching the teacher has linked the material of the Indigenous Toana tradition with the material in the textbook, contextualization is carried out by bringing up the narrative of ethnic diversity in Mempawah and the history of the Toana Tradition in Karyaaan Mempawah. Contextualization produces feedback in the form of student responses to the importance of maintaining unity in differences, besides contextualization is oriented towards growing love for local culture.